Rare presentation of urachal remnant with suprapubic sinus: A case report - Sarah Cairo; Gabriella Grisotti; Hanmin Lee (Urology Case Reports)
Incomplete obliteration of the allantois during development gives rise to urachal remnants. Presentation is variable and can range from draining umbilicus to chronic granuloma to acute infection requiring management with antibiotics and surgical excision. High index of suspicion is required to diagnoses more unusual presentations. This is a report on a case of urachal remnant presenting as a suprapubic sinus in a pediatric patient.